Assessment of Stroke Outcome Based on Initial Stroke Severity Measured on Different Stroke Severity Scales - Quddus, Abdul; Rahman, Matiur; Ahmed, Faisal; Mondol, Badrul Alam; Siddiqui, Md Mahmudur Rahman (Journal of Medicine, 2010)
Background: Stroke is the second most common cause of death globally and the major cause of disability. Though a number of studies have been conducted on stroke outcome and recovery of walking function, the list and effects of predictive factors are still a major challenge to stroke rehabilitation. Materials and methods: This was a randomized prospective study to evaluate whether initial stroke severity influences the stroke outcome. The patients were categorized after CT scan into two groups (group I- infarction type and group II haemorrhagic type). Initial stroke severity was evaluated in Scandinavian Stroke Scale (SSS). Functional status was evaluated after admission in Functional Independence Measure (FIM), Barthel Index (BI) and Short Form- 36 (SF- 36).To see the outcome in relation to time patients were evaluated with FIM, BI and SF- 36 four weeks after discharge. Results: Analysis of Scandinavian Stroke Scale indicated that the overall score was higher among the patients with cerebral infarct (mean score 29.25) compared to patients with cerebral hemorrhage (mean score 20.08) and the mean difference was statistically significant (p<0.001). Analysis of Barthel Index indicated that the percentage of improvement was significantly high among the patients with cerebral hemorrhage compared to cerebral infarct in terms of transfers from bed to chair or vice versa (p<0.001). However, improvement was also high among the patients with cerebral hemorrhage as well as cerebral infarct, but the difference was not statistically significant (p>0.05) Conclusion: This study indicates that initial motor, sensory and cognitive impairment can be good predictor in amount and time period of recovery of mobility function and other aspect in acute stroke patients, as data shows that milder the initial impairment faster and more is the recovery. Keywords: Stroke; cerebrovascular accident; outcome assessment DOI: 10.3329/jom.v11i2.5460 J MEDICINE 2010; 11 : 137-142